Creating dynamic schools through mentoring, coaching, and collaboration - Carr, Judy F.; Harris, Douglas E.; Herman, Nancy, 1950- (Alexandria, VA : Association for Supervision and Curriculum Development, 2005)
Explains how schools can be transformed into dynamic learning communities through the implementation of mentoring, coaching, and collaboration programs for students and teachers.
Includes bibliographical references (p. 158-161) and index.
Adult
Keywords: Group work in education; Mentoring in education; School supervision; Cooperative learning; Mentoring in education; School supervision